Nanotrumpets and circularly polarized luminescent nanotwists hierarchically self-assembled from an achiral C3-symmetric ester. Issue 32 (5th April 2018) - Sang, Yutao; Duan, Pengfei; Liu, Minghua
Abstract : An achiral C 3 -symmetric molecule was found to self-assemble into various hierarchical nanostructures such as nanotwists, nanotrumpets and nanobelts, in which the twisted fibers showed supramolecular chirality as well as circularly polarized luminescence although the compound is achiral. Abstract : An achiral C 3 -symmetric molecule was found to self-assemble into various hierarchical nanostructures such as nanotwists, nanotrumpets and nanobelts, in which the twisted fibers showed supramolecular chirality as well as circularly polarized luminescence although the compound is achiral.